Immune Regulation in Periodontal Disease: A Review - Manoj Kumar1, Lora Mishra2, Saurav Panda1, Anurag Satpathy3, Abhaya Chandra Das1, Gatha Mohanty4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
It is an established fact that dental plaque as a biofilm is responsible for various types of gingival andperiodontal diseases. It is a multifactorial disease in which one of the important components is the hostdefense mechanism. Through many years of research, it has now been established that the bacteria alone arenot sufficient to cause the disease, it’s only when they evade the host defense, and in the course of protectingthe host, its immune system acts against the tissues resulting in native periodontal tissue damage. Thisreview tries to gain insight into the complex immune mechanisms which take place during the pathogenesisof periodontal diseases.